2017
DOI: 10.1111/gbi.12235
|View full text |Cite
|
Sign up to set email alerts
|

Climate and geochemistry as drivers of eucalypt diversification in Australia

Abstract: Eucalypts cover most of Australia. Here, we investigate the relative contribution of climate and geochemistry to the distribution and diversity of eucalypts. Using geostatistics, we estimate major element concentrations, pH, and electrical conductivity at sites where eucalypts have been recorded. We compare the median predicted geochemistry and reported substrate for individual species that appear associated with extreme conditions; this provides a partial evaluation of the predictions. We generate a site-by-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Tests for phylogenetic localization of salinity and alkalinity tolerance would be worthwhile. Within ES 1, rhizosphere adaptations may be a key trait to cope with the annual extremes of cyclically waterlogged and parched tropical monsoon soils (Bui et al , ). Soil pH tends to decrease with rainfall: tropical monsoon soils tend to be acidic, whereas those to the south are often more alkaline (Ahren et al , ; Henderson et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests for phylogenetic localization of salinity and alkalinity tolerance would be worthwhile. Within ES 1, rhizosphere adaptations may be a key trait to cope with the annual extremes of cyclically waterlogged and parched tropical monsoon soils (Bui et al , ). Soil pH tends to decrease with rainfall: tropical monsoon soils tend to be acidic, whereas those to the south are often more alkaline (Ahren et al , ; Henderson et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Macroevolutionary patterns have been linked to historical trends in global and regional climate in many Australian lineages, including elevated speciation in arid‐zone pygopodoid geckos (Brennan & Oliver, ), macropods (Couzens & Prideaux, ), cockroaches (Beasley‐Hall et al , ), and cicadas (Owen et al , ). In plants, the eucalypts provide evidence that climate and historical events are important in explaining species distribution and turnover at the continental scale (Ladiges et al , ; Bui et al , ), and Hakea has expanded coincident with a transition to more open, drought and fire‐prone habitats promoted by aridification (Lamont et al , ; Cardillo et al , ). Aridity also drove the evolution of embolism resistance in Australian Callitris (Larter et al , ) and xeromorphy in other lineages (Hill & Brodribb, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bui et al (2017) found that incorporating soil variables with climate was efficient for defining the distribution of Eucalyptus species and strongly influenced some specific species in taxonomic sections (e.g., Aromatica and Dumaria), although that climate was more important factor. These results are similar to Martinson et al (2011), who used Maxent to model the distributions of 30 species, including shrubs, across arid areas of North America using climate and soil variables.…”
Section: Discussionmentioning
confidence: 99%
“…After the vicariance, the eudesmids radiated into the north-western arc of Australia, and the monocalypts radiated around the south-eastern arc. Bui et al (2017) noted that soil geochemistry was influential in the turnover of monocalypt species around the south-east. Further, the eudesmids and 10 moncalypts did not adapt to grow on the soil created by the inland sea, and only some symphyomyrts adapted and radiated into that part of Australia.…”
Section: Modern Distributions: Eudesmids + Monocalyptsmentioning
confidence: 99%
“…Ladiges et al (2003) suggested that eucalypt species are breaking into fragmented ranges, which could easily be a driver of diversifying large 45 widespread species into isolated populations that become unique entities. Bui et al (2017) suggested that climate and geochemistry are major factors in controlling the current distribution of eucalypt species. By combining different climate with a mosaic of soil types, it is possible to create a 50 great number of niches into which the ancestral taxa could spread and then diversify.…”
mentioning
confidence: 99%